Molecular characterization of silver-stearate nanoparticles (AgStNPs): A hydrophobic and antimicrobial material against foodborne pathogens - Bakirdere, Sezgin; Yilmaz, Mustafa Tahsin; Tornuk, Fatih; Keyf, Seyfullah; Yilmaz, Azime; Sagdic, Osman; Kocabas, Bunyamin (ELSEVIER, 2015)
In this study, silver-stearate nanoparticles (AgStNPs) have been produced from silver nitrate solutions by replacing the nitrate by stearate ions and then reducing by thermal treatment. AgStNPs were characterized by particle size, zeta-potential, ATR-FTIR, contact angle and SEM (scanning electron microscopy) analyses. The mean particle size and zeta potential of AgStNPs were determined to be 69.22 +/- 730 nm and +8.02 +/- 0.88 mV. ATR-FTIR analysis showed characteristic IR bands of stearate, revealing the two strong peaks at 2848 and 2915 cm(-1) associated to symmetric (nu(s)(CH2)) and asymmetric (nu(as)(CH2)) stretching vibrations of methylene groups, respectively. On the other hand, the scissoring and rocking modes of methylene group were observed at 1470 and 718 cm-1, respectively. Nanomorphological characterization by SEM revealed a layered morphology of AgStNPs. Contact angle measurements demonstrated that a contact angle of water drop on glass coated with AgStNPs was found to be 108.76 degrees, which proved the strong hydrophobic properties of AgStNPs. AgStNPs seemed to be very effective in inhibiting foodborne pathogens (Salmonella Typhimurium, Escherichia coli O157:H7, Staphylococcus aureus, Listeria monocytogenes and Candida albicans). The results suggest the use of AgStNPs as a coating material to reduce biofilm or biofouling formation in terms of achieving appropriate food contact surfaces and higher hygiene/easier sanitation due to their strong hydrophobic and antimicrobial properties. (C) 2015 Published by Elsevier Ltd.
Keywords: Silver stearate nanoparticles; Molecular and morphological characterization; Hydrophobicity; Antimicrobial properties; Foodborne pathogens; NORMAL-ALKYL CHAINS; H STRETCHING MODES; LISTERIA-MONOCYTOGENES; BACTERIAL BIOFILMS; ESCHERICHIA-COLI; SURFACES; MEMBRANES; TOXICITY; LONG; NANOCOMPOSITES; Food Science & Technology